Infantile hemangioendothelioma treated with high dose methylprednisolone pulse therapy. - Park, E. A. (Korean Academy of Medical Sciences, 2001)
Infantile hemangioendothelioma is a severe disease with a high mortality. It is characterized by multiple hemangioma affecting the skin and visceral organs. We report that high doses of methylprednisolone pulse therapy improved symptoms and signs of infantile hemangioendothelioma in a male neonate, and completely resolved the hepatic and cutaneous hemangioendothelioma on follow up.